Two integral theorems on a large deviations in the multi-dimensional case - Vilkauskas, L. (Lithuanian Mathematical Journal, 1963)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Л. Вилкаускас. Две интегральные теоремы о больших уклонениях в многомерном случаеL. Vilkauskas. Dvi integralinės teoremos apie didelius atsilenkimus daugiamačiu atveju